High resolution WRF climatic simulations for the Iberian Peninsula: Model validation. (August 2016) - Marta-Almeida, Martinho; Teixeira, João C.; Carvalho, Maria J.; Melo-Gonçalves, Paulo; Rocha, Alfredo M.
Abstract: A high resolution atmospheric modelling study was done for a 20-year recent historical period. The dynamic downscaling approach adopted used the Max Planck Institute Earth System Model (MPI-ESM) to drive the WRF running in climate mode. Three online nested domains were used covering part of the North Atlantic and Europe, with a resolution 81 km, and reaching 9 km in the innermost domain which covers the Iberian Peninsula. This paper presents the validation of the WRF configuration, which is based on historic simulations between 1986 and 2005 and observational datasets of near surface temperature and precipitation for the same period. The validation was done in terms of comparison of probability distributions between model results and observations, as daily climatologies, spatially averaged inside subdomains obtained with cluster analysis of the observations, for each of the four seasons. In addition, Taylor diagrams are presented for each of the seasons and subdomains. This validation approach was repeated with the results of a new WRF simulation with the same parameterisations but forced by the ERA-Interim reanalysis. The capacity of the MPI-ESM driven WRF configuration to compare with observations and in a manner similar to the ERA-Interim driven WRF, ensures the capacity of the configuration for climate and climate change studies. Considering the difficulty to simulate extremes in long term simulations, the results showed a comfortable comparison of both models (forced by climate model and reanalysis results) with observations. This provides us confidence on the continuity of using the MPI-ESM driven WRF configuration for climate studies. Highlights: High resolution dynamic downscaling for the Iberian Peninsula. Two simulations for recent historic period driven by ERA-Interim and by MPI-ESM. Taylor diagrams and estimation of probability distributions inside subdomains obtained by cluster analysis. Seasonal comparison of model results with near surface temperature and precipitation. Validation of MPI-ESM as WRF forcing for climate simulations of future scenarios.